Peran Seminar Pendidikan dalam Meningkatkan Kesadaran Remaja Terhadap Pencegahan Kenakalan Remaja di Desa Cinangneng - Maturidi; Uswatiyah, Wiwi; Ahmad, Ery Subaeri; Asila, Reni Nurul; Damayanti, Suci (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This study aims to determine the role of educational seminars as a means of socialization in preventing juvenile delinquency. The method used was descriptive qualitative, with observation and documentation techniques. The activity took place at Cendekia Cinangneng Junior High School, Bogor Regency, in August 2025, with approximately 200 students participating. The seminar used a lecture and question-and-answer method, discussing the definition, causes, impacts, and steps to prevent juvenile delinquency. The results showed that students participated enthusiastically, as evidenced by their attentiveness during the presentation and active participation in the discussion. This activity was able to increase students' understanding and raise awareness to avoid deviant behavior. Thus, educational seminars are effective as a means of socialization in efforts to prevent juvenile delinquency.